Land acquisition for industrialization and compensation of displaced farmers - Maitreesh Ghatak; Dilip Mookherjee (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
This paper addresses the question of how farmers displaced by acquisition of agricultural land for the purpose of industrialization ought to be compensated. Prior to acquisition, the farmers are leasing in land from a landlord, either a private owner or a local government. There are three sets of relevant incentive effects in the model: the decision of the landlord to sell the land ex post to an industrial developer, and ex ante incentives of tenants and landlord to make specific investments in agricultural quality of the land. Our main result is that under a broad class of circumstances, efficiency considerations require farmers be over-compensated for their loss of agricultural income in the event of conversion.
Keywords: D23; O13; Q15; 330; land acquisition; compensation; exchange rights; incentives; industrialization; Agrarboden; Bodennutzung; Industrialisierung; Grundbesitz; Mexiko